Theopolitan Worship: Sebuah Respon terhadap Kerinduan Generasi Z Indonesia akan Good Life - Atmoko, Ricky (Veritas : Jurnal Teologi dan Pelayanan, 2023)
A good life is a picture of the ideal life that drives all our decisions and habits. Based on various research results from home and abroad, the author shows that Generation Z Indonesia has the following image of a good life: a life full of entertainment, a consumptive lifestyle, and financial stability. The author proposes the concept of theopolitan worship as a means of calibrating the good life of generation Z Indonesia through the local church. First of all, the author constructs the concept of theopolitan worship by bringing together Peter J. Leithart’s thoughts on theopolitan vision, reading, and liturgy. Theopolitan worship is a worship liturgy based on biblical narratives that redeem culture and move the church to play an active role in this world. Next, the author provides some support from neurological studies related to worship that triggers several neurotransmitters such as dopamine, serotonin, and oxytocin. Finally, the author explains the impact of the Word on entertainment and the impact of Holy Communion on the consumerism and financial stability of generation Z Indonesia.